Molecular Mechanisms for Pathophysiology and Therapy of Cardiac Dysfunction in Heart Failure - Dhalla, Naranjan S; Elimban, Vijayan; Adameova, Adriana Duris; Goyal, Ramesh K (Scripta Medica, 2025)
Extensive work over the past 6 decades in the field of cardiovascular medicine has revealed that haemodynamic, hormonal, metabolic, cellular and molecular mechanisms of heart failure are not only complex but are also dependent upon the type and stage of heart disease. Although various agents such as β-adrenoreceptor blockers, angiotensin converting enzyme inhibitors, angiotensin II receptor antagonists and vasodilators are available for the treatment of heart failure, these interventions delay the progression of heart failure without reducing mortality and morbidity. In this article, literature on the pathophysiology of heart failure due to myocardial infarction and haemodynamic overload to identify molecular targets for future drug development is reviewed. Particularly, objective was to focus on the mechanisms of heart failure involving pathways for the generation of oxidative stress, myocardial inflammation and Ca2+-handling abnormalities. It is evident that elevated levels of plasma vasoactive hormones and growth factors as well as increased preload and afterload play critical roles in stimulating various signal transduction pathways for the occurrence of increased ventricular wall stress, cardiac remodelling and subsequent cardiac dysfunction. These alterations are associated with development of oxidative stress, myocardial inflammation, endothelial dysfunction, metabolic defects, intracellular Ca2+-handling abnormalities, apoptosis, fibrosis and changes in the extracellular matrix. In view of such pathogenic abnormalities in failing hearts, it is suggested these parameters may serve as excellent targets for drug development for the therapy of heart failure. In addition, there occurs activation of proteases and phospholipases as well as depression in cardiac gene expression for the induction of subcellular remodelling in failing hearts and thus interventions affecting these parameters may also be considered to exert beneficial effects in heart failure. There is also an urgent need to develop some existing and newer agents such as metabolic inhibitors, antioxidants and sodium-glucose cotransporter-2 inhibitors as well as gene and RNA based therapies for the treatment of heart failure.